The effect of weight training on the factors involved in fat metabolism in obese and overweight women - Akbar Sazvar; Yaghoub Mehrialvar; Fahime Erfaniadab (فصلنامه ابن سینا)
Background: The role of exercise intensity on the changes related to the health and appetite involved in the metabolism of individuals is unclear. the aim of this study was to investigate the effect of traditional resistance training with high-intensity periodicity on the factors involved in fat metabolism in obese and overweight women. Materials and methods: From among obese and overweight women, 30 persons were selected in an available method and randomly divided into three groups of high-intensity interval resistance training (45 minutes), traditional resistance training (75 minutes), and control . After the initial sampling, the intervention groups were active for 12 weeks. Blood samples were taken 48 hours after the last training session to remove the response to the last training session. Results: The results showed that ghrelin, weight, fat percentage, and body mass index in high-intensity interval resistance training group were significantly lower than all other groups (p<0.05). There is a significant increase in serum adiponectin in the traditional group and high-intensity interval resistance training group compared to the control group. The increase in nesfatin-1 in the high-intensity interval resistance training group led to a significant difference with the control group (p<0.05), but compared to the traditional group, these differences were not significant. Conclusion: It seems that exercise intensity is an important factor influencing changes in fat metabolism and appetite control in obese women groups. However, further research is needed to reach a definitive conclusion.